An agency-based model of executive and metacognitive regulation - Tomasello, Michael (Frontiers in Developmental Psychology, 2024)
In the context of agentive decision making and action, both executive and metacognitive processes serve self-regulatory functions -just on different hierarchical tiers. In the agency-based model proposed here executive processes monitor and control action and attention from an executive tier of operation, and metacognitive processes monitor and control those executive processes from a second-order metacognitive tier of operation -both with the function of facilitating effective and efficient behavioral decisions. Each is best conceptualized as comprising three key components: (i) what is regulated, (ii) how, via what processes, is it regulated, and (iii) where, in what cognitive workspace, is it regulated -either in individual or in shared agencies. Developmentally, evidence is presented that executive processes for regulating both individual and joint agencies emerge only after 9-12 months of age, and metacognitive processes for regulating both individual and collective agencies emerge only after 3-4 years of age. Cognitive flexibility, as an important outcome, derives from the child's attempts to metacognitively regulate differing social perspectives within shared agencies.